INNOVATIVE APPROACHES TO STUDYING AND LEARNING – MAPPING OF THE FAIRY TALE GOLDEN BIRD ATU 550 (Philological Studies, 2019)
The survey is the case study of Slovenian children’s literary from 1848 / 50-2018 based on different variants of fairy tale Zlata ptica Golden Bird in Slovenian literary culture. In the first part of the research are presented variants of fairy tale in different cultures. The case study of fairy tale Zlata ptica Golden Bird, is contribution to put spatial context in literary culture based on Slovenian folk tale. Based on the mapping of the Zlata ptica Golden Bird as a study case of the fairy tale type ATU 550 and ATU 551 and the variants in different cultures (ATU 550 [120] and ATU 551 [90]) are presented. The study case is an example of the spacial mapping into pedagogical context, from kindergarten to primary and secondary school. In the paper are furthermore an example of mapping with Erasmus students (case study: video R. Trkaja, Lepa Vida Vida the Beautiful, 2017) and the mapping of Slovenian literary culture (cultural heritage) in intercultural context. In conclusion and discussion, are presented results of applying special mapping in pedagogical context, with the goals to mapping Slovenian fairy tale in international context.
Keywords: mapping, fairy tales, Golden Bird Zlata ptica, ATU 550, Vida the Beautiful Lepa Vida, Student Translators, Erasmus students